Exploring Creativity in English Writing by Using Instagram: University Students Perceptions - Kamal Yusuf; Nikmatul Jazilah (State Institute for Islamic Studies IAIN of Metro, 2020)
Instagram is one of the social media platforms that used as a media for educational purposes. This study aimed at investigating university students' perceptions of using Instagram as an online platform to explore their creativity in English writing skill. The study used a quantitative research design. The participants of this study were students of the English Education Department of Universitas Islam Negeri Surabaya, who took a Writing English course and used Instagram in their learning activity. The questionnaire was used to collect data of this present research in the form of five-point Likert scale statements that expressed in strongly agree, agree, neutral, disagree, and strongly disagree. The descriptive quantitative were conducted on the data of analyzing the students' perceptions of using Instagram to know their responses. The findings indicated that the students demonstrated positive perceptions in using Instagram to interact with their lecture and classmates on Instagram to improve their English writing ability. The result of this research can inform that the use of Instagram in teaching writing can also shape them to become more creative and enjoyable in English writing learning.